K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

13 tháng 6 2017

4 + x = 7 - 2x

4 + x + 2x = 7

4 + 3x = 7

3x = 7 - 4

3x = 3

x = 3 : 3

x =1

13 tháng 6 2017

5 + x = 8,3 + 4,7 - x

5 + x + x = 8,3 + 4,7

5 + 2x = 13

2x = 13 -  5

2x = 8

x = 8 : 2

x= 4

28 tháng 10 2020

 11 x 10 - 10 x 9 + 9 x 8 - 8 x 7 + 7 x 6 - 6 x 5 + 5 x 4 - 4 x 3 + 3 x 2 - 2 x 1 = 60

10 tháng 6 2017

1. 41/7 - x = 25/9

=> x = 41/7 - 25/9

=> x = 194/63

2. 3x = 12,8

=> x = 12,8 : 3

=> x = 64/15

3. 41/2 x = 5

=> x = 5: 41/2

=> x = 10/41

4. 3/4 x = 1

=> x = 1: 3/4

=> x = 3/4

5. 4/5 : x = 3

=> x = 4/5 : 3

=> x = 4/15

6. 12/x = 4

=> x = 12/4

=> x = 3

7. 4/7 : x = 4/7

=> x = 4/7 : 4/7

=> x = 1

8. 2x - 3/4 = 7/8

=> 2x = 7/8 + 3/4

=> 2x = 13/8

=> x = 13/8 : 2

=> x =13/16

Ruby Chan :))

10 tháng 6 2017

1, \(4\frac{1}{7}-x=2\frac{5}{9}\)

\(\frac{4\times7+1}{7}-x=\frac{2\times9+5}{9}\)

\(\frac{29}{7}-x=\frac{23}{9}\)

\(x=\frac{29}{7}-\frac{23}{9}\)

\(x=\frac{261}{63}-\frac{161}{63}\)

\(x=\frac{100}{63}\)

2, \(3\times x=12,18\)

\(x=12,18\div3\)

\(x=4,06\)

3, \(4\frac{1}{2}\times x=5\)

\(\frac{4\times2+1}{2}\times x=5\)

\(\frac{9}{2}\times x=5\)

\(x=5\div\frac{9}{2}\)

\(x=\frac{5\times2}{9}=\frac{10}{9}\)

4, \(\frac{3}{4}\times x=1\)

\(x=1\div\frac{3}{4}\)

\(x=\frac{1\times4}{3}=\frac{4}{3}\)

5, \(\frac{4}{5}\div x=3\)

\(x=\frac{4}{5}\div3\)

\(x=\frac{4}{5\times3}=\frac{4}{15}\)

6,\(\frac{12}{x}=4\)

\(x=12\div4\)

\(x=3\)

7, \(\frac{4}{7}\div x=\frac{4}{7}\)

\(x=\frac{4}{7}\div\frac{4}{7}\)

\(x=1\)

8, \(2x-\frac{3}{4}=\frac{7}{8}\)

\(2x=\frac{7}{8}+\frac{3}{4}\)

\(2x=\frac{7}{8}+\frac{6}{8}\)

\(2x=\frac{13}{8}\)

\(x=\frac{13}{8}\div2\)

\(x=\frac{13}{8\times2}=\frac{13}{16}\)

20 tháng 7 2019

a. \(\frac{-3}{2}-2x+\frac{3}{4}=-22\)2

=> \(-2x=-22+\frac{3}{2}-\frac{3}{4}\)

=> \(-2x=\frac{-85}{4}\)

=> \(x=\frac{-85}{4}:\left(-2\right)\)

=> \(x=\frac{85}{8}\)

b. \(\left(\frac{-2}{3}x-\frac{3}{5}\right).\left(\frac{3}{-2}-\frac{10}{3}\right)=\frac{2}{5}\)

=> \(\left(\frac{-2}{3}x-\frac{3}{5}\right).\frac{-29}{6}=\frac{2}{5}\)

=> \(\frac{-2}{3}x-\frac{3}{5}=\frac{2}{5}:\left(\frac{-29}{6}\right)\)

=> \(\frac{-2}{3}x-\frac{3}{5}=\frac{-12}{145}\)

=> \(\frac{-2}{3}x=\frac{-12}{145}+\frac{3}{5}\)

=> \(\frac{-2}{3}x=\frac{15}{29}\)

=> x = \(\frac{15}{29}:\frac{-2}{3}\)

=> x = \(\frac{-45}{58}\)

2 tháng 11 2023

a) \(\dfrac{5}{7}\times\dfrac{5}{9}+\dfrac{4}{9}\times\dfrac{5}{7}\)

\(=\dfrac{5}{7}\times\left(\dfrac{4}{9}+\dfrac{5}{9}\right)\)

\(=\dfrac{5}{7}\times1\)

\(=\dfrac{5}{7}\)

b) \(\dfrac{1}{10}+\dfrac{5}{9}+\dfrac{4}{9}+\dfrac{9}{10}-1\)

\(=\left(\dfrac{5}{9}+\dfrac{4}{9}\right)+\left(\dfrac{1}{10}+\dfrac{9}{10}-1\right)\)

\(=1+0\)

\(=1\)

c) \(\dfrac{5}{7}\times\dfrac{5}{9}+\dfrac{4}{9}\times\dfrac{5}{7}+\dfrac{2}{7}\)

\(=\dfrac{5}{7}\times\left(\dfrac{5}{9}+\dfrac{4}{9}\right)+\dfrac{2}{7}\)

\(=\dfrac{5}{7}+\dfrac{2}{7}\)

\(=1\)

d) \(\dfrac{2}{7}+\dfrac{2}{8}+\dfrac{1}{4}+\dfrac{1}{7}+\dfrac{4}{7}\)

\(=\left(\dfrac{2}{8}+\dfrac{1}{4}\right)+\left(\dfrac{2}{7}+\dfrac{1}{7}+\dfrac{4}{7}\right)\)

\(=\left(\dfrac{1}{4}+\dfrac{1}{4}\right)+1\)

\(=\dfrac{1}{2}+1\)

\(=\dfrac{3}{2}\)

e) \(\dfrac{4}{5}+\dfrac{3}{10}+\dfrac{2}{10}+0,7\)

\(=\dfrac{4}{5}+\dfrac{5}{10}+\dfrac{7}{10}\)

\(=\dfrac{4}{5}+\dfrac{12}{10}\)

\(=\dfrac{4}{5}+\dfrac{6}{5}\)

\(=\dfrac{10}{5}\)

\(=2\)

g) \(362\times728+326\times272\)

\(=326\times\left(728+272\right)\)

\(=326\times1000\)

\(=326000\)